Efficacy and Safety of Roluperidone for the Treatment of Negative Symptoms of Schizophrenia. (25th February 2022) - Davidson, Michael; Saoud, Jay; Staner, Corinne; Noel, Nadine; Werner, Sandra; Luthringer, Elisabeth; Walling, David; Weiser, Mark; Harvey, Philip D; Strauss, Gregory P; Luthringer, Remy
Abstract: Background: This is a placebo-controlled multi-national trial of roluperidone, a compound with antagonist properties for 5-HT2A, sigma2, and α1A -adrenergic receptors, targeting negative symptoms in patients with schizophrenia. This trial follows a previous trial that demonstrated roluperidone superiority over placebo in a similar patient population. Methods: Roluperidone 32 mg/day, roluperidone 64 mg/day, or placebo was administered for 12 weeks to 513 patients with schizophrenia with moderate to severe negative symptoms. The primary endpoint was the PANSS-derived Negative Symptom Factor Score (NSFS) and the key secondary endpoint was Personal and Social Performance scale (PSP) total score. Results: NSFS scores were lower (improved) for roluperidone 64 mg compared to placebo and marginally missing statistical significance for the intent-to-treat (ITT) analysis data set ( P ≤ .064), but reached nominal significance ( P ≤ .044) for the modified-ITT (m-ITT) data set. Changes in PSP total score were statistically significantly better on roluperidone 64 mg compared to placebo for both ITT and m-ITT ( P ≤ .021 and P ≤ .017, respectively). Conclusions: Results of this trial confirm the potential of roluperidone as a treatment of negative symptoms and improving everyday functioning in patients with schizophrenia. Study registration: Eudra-CT: 2017-003333-29; NCT03397134.